Efecto del vendaje neuromuscular en el equilibrio y la locomoción en adultos mayores: revisión sistemática - Samaniego Vivanco, María Sol (2020)
Objectives: To analyze the effects of neuromuscular taping on balance and locomotion in older adults, systematic review…